Paradoxical effects of trichostatin A: inhibition of NF-Y-associated histone acetyltransferase activity, phosphorylation of hGCN5 and downregulation of cyclin A and B1 mRNA. - Nair, A; Boersma, L; Schiltz, L; Chaudhry, M; Muschel, R; Chaudry, A (2001)
Trichostatin A (TSA), an inhibitor of histone deacetylase (HDAC), is widely used to study the role of histone acetylation in gene expression, since genes that use histone acetylation as a means of regulating expression may be up regulated when TSA is added. In this study, however, we show that TSA has an unexpected paradoxical effect leading to inhibition of NF-Y-associated histone acetyl transferase (HAT) activity and phosphorylation of the HAT, hGCN5. TSA treatment of cells resulted in diminished levels of NF-Y-associated HAT activity without changes in NF-Y(A) amount. hGCN5 is one of the HATs known to associate with NF-Y. The association of hGCN5 with NF-Y was not altered by TSA treatment. The enzymatic activity of hGCN5 is known to be inhibited by phosphorylation. TSA treatment of Hela cells resulted in phosphorylation of hGCN5. Exposure of the NF-Y immunoprecipitates from TSA-treated cells to a phosphatase resulted in enhanced HAT activity. We have also shown that the mRNA levels of several genes, cyclin B1 and cyclin A, are downregulated by TSA; these effects do not require protein synthesis and the downregulation of cyclin B1 by TSA occurs through transcription. These results suggest that TSA can have contradictory effects, on one hand stimulating HAT activity in general by inhibition of HDACs, but also resulting in inhibition of NF-Y-associated HAT activity and phosphorylation of hGCN5.